Fagopyrum urophyllum (Polygonaceae), a new record for India and notes on its typification - Das, M.; Dash, S. S. (Rheedea, 2021)
Fagopyrum urophyllum (Bureau & Franch.) H.Gross (Polygonaceae), is reported here as a new record to the Indian flora. The species, earlier known only from China, has been collected from the Namchi and Tendong region of the South district, Sikkim, India at an altitude of 1845 m. A description along with illustration, photo plate of dissected flower parts, and a distribution map in India is provided herewith. Notes on the lectotypification of the name Fagopyrum urophyllum and a national conservation status of this species in India is also provided.